2018
DOI: 10.1111/jan.13851
|View full text |Cite
|
Sign up to set email alerts
|

Developing and validating learning domains, competencies, and evaluation items for global health clinical immersion practicums for graduate‐level nursing programs

Abstract: Global health clinical learning practicums are essential for graduate-level preparation of nurses. Learning domains, competencies, and evaluation tools need to be adopted and empirically tested by international and national nursing associations. The results of this study need further testing to aid these associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The first key theme was direct engagement and application of learning in clinical or field settings. For clinical settings, this could include practice with standardized patients, supervised clinical activities, other engagement with host team members, or similar apprenticeship models [ 34 , 50 , 52 , 54 ]. For non-clinical field activities, these field placements included participation in activities from community diagnosis and program planning through to project evaluation [ 44 , 51 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first key theme was direct engagement and application of learning in clinical or field settings. For clinical settings, this could include practice with standardized patients, supervised clinical activities, other engagement with host team members, or similar apprenticeship models [ 34 , 50 , 52 , 54 ]. For non-clinical field activities, these field placements included participation in activities from community diagnosis and program planning through to project evaluation [ 44 , 51 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…well as reflections with peers as a strategy to strengthen the absorption of curricula [34,44,50,51,54,62].…”
Section: Plos Onementioning
confidence: 99%
“…The Yale DNP projects are evidence‐based and have focused on topics such as senior nurse leadership, health policy advocacy, innovations in healthcare delivery and operations improvement. Globally relevant topics including workforce development and management and resource allocation at YSN have included ‘Indian Health Funding: Time for Change’, ‘An Interprofessional Model of Care for an Underserved Primary Care Population’, ‘A Model of a Nurse‐Run School Based in Nambale Magnet School, Nambale, Kenya’ and ‘Developing and Validating Learning Domains, Competencies, and Evaluation Items for Global Health Clinical Immersion Practicums for Graduate‐Level Nursing Programs’ (Kelly & Lazenby ). The YSN DNP programme meets the academic standards and expectations of Yale University, one of the world's oldest universities, with a mission to ‘improve the world now and for future generations’.…”
Section: Yale School Of Nursing Systems Leadership Programme Exemplarmentioning
confidence: 99%
“…Globally relevant topics including workforce development and management and resource allocation at YSN have included 'Indian Health Funding: Time for Change', 'An Interprofessional Model of Care for an Underserved Primary Care Population', 'A Model of a Nurse-Run School Based in Nambale Magnet School, Nambale, Kenya' and 'Developing and Validating Learning Domains, Competencies, and Evaluation Items for Global Health Clinical Immersion Practicums for Graduate-Level Nursing Programs'(Kelly & Lazenby 2018). The YSN DNP programme meets the academic standards and expectations of Yale University, one of the world's oldest…”
mentioning
confidence: 99%
“…While relatively new to public health education, the value of experiential learning in education is well described in the literature relating to other allied health fields such as medicine, nursing and social work (4)(5)(6). Akin to these sectors, public health occurs primarily in the field and it has been demonstrated that experiential learning is critical to capacity building in public health education (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%